This Could Be the Start of Something Big : How Social Movements for Regional Equity Are Reshaping Metropolitan America - Pastor, Manuel, 1956- (Book collections on Project MUSE., 2009)
For nearly two decades, progressives have been dismayed by the steady rise of the right in U.S. politics. Often lost in the gloom and doom about American politics is a striking and sometimes underanalyzed phenomenon: the resurgence of progressive politics and movements at a local level. Across the country, urban coalitions, including labor, faith groups, and community-based organizations, have come together to support living wage laws and fight for transit policies that can move the needle on issues of working poverty. Just as striking as the rise of this progressive resurgence has been its reception among unlikely allies. In places as diverse as Chicago, Atlanta, and San Jose, the usual business resistance to pro-equity policies has changed, particularly when it comes to issues like affordable housing and more efficient transportation systems. To see this change and its possibilities requires that we recognize a new thread running through many local efforts: a perspective and politics that emphasizes "regional equity." Manuel Pastor Jr., Chris Benner, and Martha Matsuoka offer their analysis with an eye toward evaluating what has and has not worked in various campaigns to achieve regional equity. The authors show how momentum is building as new policies addressing regional infrastructure, housing, and workforce development bring together business and community groups who share a common desire to see their city and region succeed. Drawing on a wealth of case studies as well as their own experience in the field, Pastor, Benner, and Matsuoka point out the promise and pitfalls of this new approach, concluding that what they term social movement regionalism might offer an important contribution to the revitalization of progressive politics in America